CD73 Attenuates Alcohol-Induced Liver Injury and Inflammation via Blocking TLR4/MyD88/NF-κB Signaling Pathway - Liu ZN; Wu X; Fang Q; Li ZX; Xia GQ; Cai JN; Lv XW (Dove Medical Press, 2022)
Zhen-Ni Liu,1- 3 Xue Wu,1- 3 Qian Fang,1- 3 Zi-Xuan Li,1- 3 Guo-Qing Xia,1- 3 Jun-Nan Cai,1- 3 Xiong-Wen Lv1- 3 1Inflammation and Immune Mediated Diseases Laboratory of Anhui Province, Anhui Institute of Innovative Drugs, School of Pharmacy, Anhui Medical University, Hefei, People's Republic of China; 2The Key Laboratory of Anti-Inflammatory and Immune Medicines, Ministry of Education, Hefei, People's Republic of China; 3Institute for Liver Diseases of Anhui Medical University, Hefei, People's Republic of ChinaCorrespondence: Xiong-Wen LvSchool of Pharmacy, Anhui Medical University, 81 Mei Shan Road, Hefei, Anhui Province, 230032, People's Republic of ChinaEmail lyuxw@ahmu.edu.cnBackground: Alcoholic liver disease (ALD) is liver damage caused by long-term drinking. Inflammation plays a central role in the progression of ALD. CD73 is a ubiquitously expressed glycosylphosphatidylinositol-anchored glycoprotein that is a key enzyme that converts ATP into adenosine. Evidence has shown that CD73 plays an important role in many diseases, but the role and mechanism of CD73 in alcohol-induced liver injury and inflammation is still unclear.Methods: The alcohol-induced liver injury and inflammation mouse model was established. The rAAV9-CD73 was used to overexpress CD73. Isolation of primary macrophages (MΦ) from the liver was conducted. The effects of CD73 on alcohol-induced liver injury and inflammation were evaluated by quantitative real‑time PCR, Western blotting, ELISA, and immunohistochemical assay. Flow cytometry was used to detect the cell cycle and apoptosis.Results: Our results showed that overexpression of CD73 can reduce alcohol-induced liver damage, lipid accumulation, and the secretion of inflammatory cytokines. pEX3-CD73 can promote RAW264.7 cells proliferation and inhibit apoptosis via suppressing the activation of TLR4/MyD88/NF-κB signaling pathway. Inhibition of TLR4 further enhanced the anti-inflammatory effect of overexpression of CD73.Conclusion: Overexpression of CD73 can reduce alcohol-induced liver injury and inflammation. CD73 may serve as a potential therapeutic target for ALD.Keywords: CD73, alcohol-induced liver injury and inflammation, TLR4/MyD88/NF-κB signaling pathway, apoptosis, RAW264.7 cells